TINJAUAN HUKUM ISLAM TERHADAP I?BAT NIKAH DALAM PERNIKAHAN SIRI DI PENGADILAN AGAMA BARRU (Studi Kasus Penetapan Nomor 253/Pdt.P/2021/PA.Br) - Siti Nur Fajriyati (Jurnal Risalah Addariyah STAI DDI Mangkoso, 2024)
The main problem of this research is how Islamic law reviews the nikah i?bat in unregistered marriages at the Barru Religious Court (case study determination number 253/Pdt.P/2021/PA.Br)? The main problem is then broken down into several sub-problems or research questions, namely: 1) What is the view of Islamic law towards i?bat nikah in siri marriages?, 2) How do judges consider the Barru Religious Court in deciding cases of i?bat nikah in siri marriages (study case determination number 253/Pdt.P/2021/PA.Br)? This type of research is classified as normative-empirical with the research approaches used being: syar'i (theology), legislation (statue approach) and cases. The data source for this research is the Judge of the Barru Religious Court. Furthermore, the data collection methods used are analysis, interviews and documentation. Then, data processing and data analysis techniques are carried out through three stages, namely: data reduction, data presentation and drawing conclusions. The results of this research show that Islamic law is of the view that marriage i?bat is something that can be done in marriages that are valid according to Islamic law. As regulated in the Compilation of Islamic Law (KHI) Article 4 which explains that if the parties are Muslim, then the marriage process carried out must be in accordance with Islamic law and the Compilation of Islamic Law (KHI) Article 7 paragraph (3) also explains that Marriage licenses that can be submitted to the Religious Court are only limited to matters relating to the existence of a marriage in the context of resolving a divorce, the loss of a Marriage Certificate, doubts about whether or not the type of marriage is valid or not, the existence of a marriage that occurred before the enactment of Law No. . 1 of 1974 and marriages carried out by those who do not have obstacles to marriage according to Law no. 1 of 1974. In the judge's consideration to determine the case of i?bat nikah, namely by fulfilling the pillars and conditions of marriage and not violating marriage prohibitions using the basis of legal considerations recognized in Indonesia, namely Law Number 1 of 1974 concerning marriage and the Compilation of Islamic Law. The implications of this research are: 1) To Religious Court Institutions, especially the Office of Religious Affairs (KUA) to provide understanding or educate the public regarding marriage registration and marriage law and its application. 2) Couples who wish to get married should report their marriage to the authorized party, namely the Marriage Registrar (VAT) to be registered in order to create order in marriage in society and to protect the rights of each party involved.